1996
DOI: 10.1007/bf02246016
|View full text |Cite
|
Sign up to set email alerts
|

The biological, social and clinical bases of drug addiction: commentary and debate

Abstract: This article summarizes the main discussions at a meeting on the biological, social and clinical bases of drug addiction focused on contemporary topics in drug dependence. Four main domains are surveyed, reflecting the structure of the meeting: psychological and pharmacological factors; neurobiological substrates; risk factors (including a consideration of vulnerability from an environmental and genetic perspective); and clinical treatment. Among the topics discussed were tolerance, sensitization, withdrawal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
167
0
7

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(175 citation statements)
references
References 271 publications
1
167
0
7
Order By: Relevance
“…If we accept the concept that some of the individuals who abuse alcohol do so in part because of the changes the drug induces in their C NS, it seems reasonable to propose that if such changes cannot be achieved with a given dose of alcohol, these individuals may consume more of the drug in an attempt to regain the wanted changes. A drug exerts its reinforcing effects via a number of distinct actions, including the ability to stimulate brain circuitries involved in the reward system and to induce symptoms of withdrawal that can only be averted by resuming drug consumption (Nestler et al, 1993;Altman et al, 1996;Koob, 1996). We suggest that our studies may provide the basis for a testable, neuroendocrine-based hypothesis of vulnerability to alcohol abuse.…”
Section: Discussionmentioning
confidence: 82%
“…If we accept the concept that some of the individuals who abuse alcohol do so in part because of the changes the drug induces in their C NS, it seems reasonable to propose that if such changes cannot be achieved with a given dose of alcohol, these individuals may consume more of the drug in an attempt to regain the wanted changes. A drug exerts its reinforcing effects via a number of distinct actions, including the ability to stimulate brain circuitries involved in the reward system and to induce symptoms of withdrawal that can only be averted by resuming drug consumption (Nestler et al, 1993;Altman et al, 1996;Koob, 1996). We suggest that our studies may provide the basis for a testable, neuroendocrine-based hypothesis of vulnerability to alcohol abuse.…”
Section: Discussionmentioning
confidence: 82%
“…Koob and Nestler, 1997) but are hypoactive in abstinent drug users (e.g. Altmann et al, 1996;Volkow et al, 2004). Disturbances of the cognitive and behavioural processes mediated by these pathways, including attribution of salience to external stimuli and inhibitory control over behaviour, may contribute both to the development of dependence and to relapse.…”
Section: Introductionmentioning
confidence: 99%
“…In smokers, for instance, Geracioti et al (1999) found abnormally low levels of a DA metabolite in cerebrospinal fluid. Reviewing an international symposium on this topic, Altmann et al (1996) concluded that "withdrawal from various drugs of abuse is associated with a reduction in dopamine transmission in the ventral striatum, an effect that is opposite to the common property of drugs of abuse to stimulate dopamine transmission. "…”
Section: Effects Of Smoking and Abstinence On Functioning Of Brain Rementioning
confidence: 99%